Comparative Genome Analysis of Uropathogenic Morganella morganii Strains - Minnullina, Leyla; Pudova, Daria; Shagimardanova, Elena; Shigapova, Leyla; Sharipova, Margarita; Mardanova, Ayslu (Frontiers in Cellular and Infection Microbiology, 2019)
Morganella morganii is an opportunistic bacterial pathogen shown to cause a wide range of clinical and community-acquired infections. This study was aimed at sequencing and comparing the genomes of three M. morganii strains isolated from the urine samples of patients with community-acquired urinary tract infections. Draft genome sequencing was conducted using the Illumina HiSeq platform. The genomes of MM 1, MM 4, and MM 190 strains have a size of 3.82-3.97 Mb and a GC content of 50.9-51%. Protein-coding sequences (CDS) represent 96.1% of the genomes, RNAs are encoded by 2.7% of genes and pseudogenes account for 1.2% of the genomes. The pan-genome containes 4,038 CDS, of which 3,279 represent core genes. 6-10 prophages and 21-33 genomic islands were identified in the genomes of MM 1, MM 4, and MM 190. More than 30 genes encode capsular biosynthesis proteins, an average of 60 genes encode motility and chemotaxis proteins, and about 70 genes are associated with fimbrial biogenesis and adhesion. We determined that all strains contained urease gene cluster ureABCEFGD and had a urease activity. Both MM 4 and MM 190 strains are capable of hemolysis and their activity correlates well with a cytotoxicity level on T-24 bladder carcinoma cells. These activities were associated with expression of RTX toxin gene hlyA, which was introduced into the genomes by a phage similar to Salmonella phage 118970_sal4.